COMPARATIVE STUDY BETWEEN MORALITY VCT LEARNING MODEL AND GI NOTING WITH ATTITUDE ON THE SUBJECT - Eka Rizky Amalia; Edi Purnomo; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2013)
This study aimed to determine whether there is a moral difference between students who are learning using model Value Clarification Technique (VCT) and students who are learning using model Group Investigation (GI) with respect to attitudes toward integrated social studies. The method used in this research is experimental research method with a comparative approach. Based on the analysis of the data obtained the following findings: (1) there is a moral difference between students who are taught using learning model Value Clarification Technique (VCT) and students who are taught using learning model Group Investigation (GI) on Integrated social studies. (2) morality student learning using learning model Value Clarification Technique (VCT) is better than either model of learning Group Investigation (GI) for students who have a positive attitude towards integrated social studies. (3) morality student learning using learning model Group Investigation (GI) is better than either model of learning Value Clarification Technique (VCT) for students who have a negative attitude towards integrated social studies. (4) there is interaction between the use of models of learning and students' attitudes to the subject of the morality Integrated IPS students.Keywords: Morality, VCT and GI, AAS.